Distribution of PAHs and n-alkanes in Klang River surface sediments, Malaysia - Bakhtiari, Alireza Riyahi; Zakaria, Mohamad Pauzi; Yaziz, Mohammad Ismail; Lajis, Md. Nordin; Bi, Xinhui; Mohamad Shafiee, Mohamad Reza; Sakari, Mahyar (Universiti Putra Malaysia Press, 2010)
Surface sediment samples were collected from five locations at the downstream of Klang River in January 2007 to examine the spatial distribution, composition, and sources of 19 parent polycyclic aromatic hydrocarbons (PAHs) and aliphatic hydrocarbon (n-alkanes) using gas chromatography-mass spectrometry. The total concentrations of the 19 PAHs in the sediments were found to range from 1304 to 2187 ng g-1 sediment. Meanwhile, total concentrations of n-alkanes ranged from 17008 to 27116 μg g-1 sediment. The concentration of n-alkanes in the sediment was significantly correlated (r = 0.991, p = 0.001) with the content of sediment organic carbon. In this study, all the sediments exhibited phenanthrene/anthracene (PHE/ANT >15) fluoranthene/(fluorantene+pyrene) (FLT/FLT+PYR < 0.4), methylphenanthrenes/phenanthrene (MP/P >1), combustion PAHs/total PAHs (CombPAH/∑19PAH <0.3), terrigenous/aquatic ratio for hydrocarbons greater than 23. The also data showed that petrogenic and natural inputs were predominant at all the locations investigated. Multiple sources of n-alkanes and PAHs in the river sediments were also explained by low carbon preference index (CPI) values, different ratios of diploptene/∑C23-C25 n-alkanes, poor correlation between diploptene and ∑C23-C25, average chain length (ACL) of 29.54 ± 0.09, correlation between CPI and ACL (r = 0.847, p= 0.035), and high ratio of naphthalene/total PAHs.